Pemertahanan Kekhasan Pengajaran Kitab Kuning pada Pondok Pesantren Martapura Kalimantan Selatan (Telaah Aspek Linguistik dan Sosiolingustik) - Hidayati, Noor Azmah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2017)
The Maintenance of the Unique Teaching of the Yellow Book At Pondok Pesantren Darussalam Martapura South Kalimantan (Review Linguistic and Sociolingustic Aspects). Pesantren as an Islamic educational institution has various characteristics. One of them is the uniqueness in teaching of yellow book, as applied in Pondok Pesantren Darussalam (PPD) Martapura. To achieve the purpose of pesantren tafaqquh fî ad-dîn, the yellow book must be mastered by santri. To master the yellow book, the element and the knowledge of yellow book are considered as the main tool. The emphasis on these two aspects also has an impact on the application of characteristic translations. The translation seems unique, rigid, and clumsy so that it is potentially difficult to understand and can even lead to misunderstandings. However, the specificity of teaching is instead maintained and can be accepted in the pesantren. This paper is intended to express how and why the specificity of yellow book teaching can survive and be maintained in PPD Martapura in terms of linguistic and sociolinguistic aspects.